Untargeted metabolomic analysis of dietary rumen-protected choline supplementation in fattening lambs - Yun, Jinyan; Zhu, Airong; You, Peihua; Sun, Xuezhao (Frontiers in Veterinary Science, 2025)
IntroductionCholine is an essential nutrient that plays a key role in lipid metabolism and growth performance in livestock.MethodsThis study investigated the effects of rumen-protected choline (RPC) supplementation on serum metabolite profiles in fattening lambs. Twenty 3-month-old hybrid rams (Small-Tailed Han × Northeast Fine-Wool; initial body weight: 15.3 ± 1.8 kg) were randomly assigned to two groups (n = 10 each): a control group (CON; 0 g RPC/kg dry matter [DM]) and an RPC group (5 g RPC/kg DM). Over a 122-day feeding period, lambs were provided ad libitum access to feed and water, with feedings at 08:00 and 15:00 daily. Serum samples were collected at the end of the trial and analyzed using untargeted metabolomics based on liquid chromatography–tandem mass spectrometry (LC-MS/MS).ResultsA wide range of metabolites were identified, including benzenoids, lipids and lipid-like molecules, nucleosides and nucleotides, organic acids, and derivatives. Pathway analysis using the Kyoto Encyclopedia of Genes and Genomes (KEGG) revealed involvement in lipid, amino acid, vitamin, and carbohydrate metabolism. Partial least squares-discriminant analysis (PLS-DA) showed clear separation between CON and RPC groups. Triacylglycerol, L-methionine, plasmenylcholine, taurocholate, 1-acyl-sn-glycero-3-phosphoethanolamine, and 1-acyl-sn-glycero-3-phosphocholine were identified as potential bio markers associated with increased hot carcass weight (HCW) and slaughter rate.DiscussionRPC supplementation significantly modulated the serum metabolome, enhancing HCW and slaughter rate, likely via lipid, amino acid, and energy metabolism pathways.